2018
DOI: 10.1038/nbt.4297
|View full text |Cite
|
Sign up to set email alerts
|

RNAi modulation of placental sFLT1 for the treatment of preeclampsia

Abstract: Preeclampsia (PE) is a placentally-induced hypertensive disorder of pregnancy that is associated with significant morbidity and mortality to mothers and fetuses. Clinical manifestations of preterm PE result from excess circulating soluble vascular endothelial growth factor receptor FLT1 (sFLT1 or sVEGFR1) of placental origin. Here we identify short interfering RNAs (siRNAs) that selectively silence the three sFLT1 mRNA isoforms primarily responsible for placental overexpression of sFLT1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(108 citation statements)
references
References 71 publications
1
105
0
2
Order By: Relevance
“…RNA sequencing studies in human placentae from pre-eclamptic pregnancies suggest that three major isoforms of the FLT1 locus contribute to sFLT1 in the circulation 190 . In 2018, researchers identified novel RNAi molecules that specifically target all of the major sFLT1 mRNAs in cell culture studies 191 . They demonstrated that a single dose of sFLT1 RNAi therapy given intravenously lowered the sFLT1 protein level by 50%, which was accompanied by a reduction in blood pressure and proteinuria in a baboon model of pre-eclampsia.…”
Section: Rna Interference-based Strategiesmentioning
confidence: 99%
“…RNA sequencing studies in human placentae from pre-eclamptic pregnancies suggest that three major isoforms of the FLT1 locus contribute to sFLT1 in the circulation 190 . In 2018, researchers identified novel RNAi molecules that specifically target all of the major sFLT1 mRNAs in cell culture studies 191 . They demonstrated that a single dose of sFLT1 RNAi therapy given intravenously lowered the sFLT1 protein level by 50%, which was accompanied by a reduction in blood pressure and proteinuria in a baboon model of pre-eclampsia.…”
Section: Rna Interference-based Strategiesmentioning
confidence: 99%
“…194 An alternative approach only tested in pre-clinical models is to knock down expression of sFlt in the placenta using interference RNA technology. 195 Other possible therapies are modifiers of endoplasmic reticulum stress, hydrogen sulphide donors, 161 and scavengers of fetal haemoglobin. 196…”
Section: Emerging Therapiesmentioning
confidence: 99%
“…Conjugation of oligonucleotides to a variety of chemical entities allows for modulation of bioavailability, tissues exposure and, in some cases, cell-type specific delivery ( 7–8 , 11 , 53 ). The recent approval of a fully chemically stabilized GalNAc siRNA, Givosiran, demonstrates the immense potential of conjugated siRNAs to treat genetic diseases ( 54 ).…”
Section: Discussionmentioning
confidence: 99%